About professional baking - Sokol, Gail (Australia : Thomson Delmar Learning, 2008)
This book provides a hands-on guide to essential professional baking techniques and practices, demonstrated by Chef Gail Sokol
Chapter 1. Mise en Place -- Chapter 2. Ingredients -- Chapter 3. Wheat Flour: The Essential Grain (and Other Flours) -- Chapter 4. The Science of Mixing -- Chapter 5. Thickeners and Stabilizers -- Chapter 6. Eggs as Thickeners -- Chapter 7. Eggs as Leaveners and Meringues -- Chapter 8. Working with Yeast in Straight Doughs -- Chapter 9. Preferments -- Chapter 10. Laminated Doughs -- Chapter 11. Working with Fats in Pies and Tarts -- Chapter 12. Using Chemical and Steam Leaveners -- Chapter 13. Quick Bread Mixing Methods -- Chapter 14. Cake Mixing Methods -- Chapter 15. Frostings -- Chapter 16. Cookies -- Chapter 17. Building Blocks with Sugar -- Chapter 18. Frozen Desserts -- Chapter 19. Chocolate -- Chapter 20. Dessert Sauces and Plating -- Chapter 21. Healthy Baking -- Chapter 22. Troubleshooting.
Includes index.
Keywords: BAKING